Saprolegnia parasitica impairs branchial phosphoryl transfer network in naturally infected grass carp (Ctenopharyngodon idella): prejudice on bioenergetic homeostasis - Baldissera M.D. (2019)
© 2019, Springer Nature Switzerland AG.Precise coupling of spatially separated intracellular adenosine triphosphate (ATP) producing and ATP-consuming exerts a key role in bioenergetic balance, and the phosphoryl transfer network, catalyzed by creatine kinase (CK), adenylate kinase (AK), and pyruvate kinase (PK), is fundamental in energetic homeostasis of tissues with high-energy requirements, as the branchial tissue. This whole system is very sensitive, and our hypothesis is that it can be altered in cases of infectious diseases in fish, such as that caused by the oomycete Saprolegnia parasitica. The effects of S. parasitica infection on gills remain poorly understood and limited only to histopathological studies. Thus, the aim of this study was to evaluate whether natural infection by S. parasitica impairs the enzymes of the phosphoryl transfer network in gills of grass carp (Ctenopharyngodon idella), as well as the pathways involved in this inhibition. In this study, we used sick carp and compared to healthy carp, fish of similar age and receiving the same feed, but allocated in different tanks. Branchial CK (cytosolic and mitochondrial) activity and ATP levels decreased in infected fish compared to uninfected on day 7 post-infection (PI), while no significant difference was observed between groups regarding branchial AK and PK activities. Branchial sodium-potassium ion pump (Na+, K+-ATPase) activity decreased in infected carp compared to uninfected on day 7 PI, while reactive oxygen species (ROS) and thiobarbituric acid reactive substance (TBARS) levels were higher. Gill histopathology revealed massive necrosis, loss of branchial epithelium, and detachment of the epithelium interlayer with structural loss of secondary lamellae. Based on these data, the impairment of CK activity elicited by S. parasitica caused an impairment in branchial energetic homeostasis, reducing the ATP availability in the gills and provoking an impairment on Na+, K+-ATPase activity. Moreover, the inhibition on CK activity appears to be mediated by ROS overproduction and lipid peroxidation, which contribute to disease pathogenesis linked to branchial tissue.